Social Commerce Platforms Role in FoMO Driven Consumption: The Hidden Psychological Toll of Continuous Use - Enginkaya, Ebru; Saglam, Munise Hayrun (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2025)
This study examines the influence of Fear of Missing Out (FoMO) on continuous usage of social commerce platforms (SCPs) and explores its psychological and behavioral ramifications within the context of attention economy. Drawing on Self-Determination Theory (SDT) and Information Overload Theory (IOT), a survey of 872 active social commerce platform (SCP) users was conducted. Structural Equation Modeling (SEM) in SmartPLS 4 was utilized to analyze direct, indirect, and moderating relationships among key constructs, including Psychological Anxiety (PA), Nomophobia (NOMO), and Problematic Social Media Use (PSMU). The results indicate that FoMO substantially drives compulsive platform usage (beta =0.453 , p < 0.001), strongly predicts PSMU (beta =0.826 , p < 0.001), and indirectly increases psychological anxiety, nomophobia, phubbing behavior, and social network fatigue. Furthermore, informational incentives (e.g., personalized content, real-time updates) significantly amplify users' anxiety, fatigue, and compulsive digital behaviors by exacerbating cognitive overload (interaction effects ranging from beta =0.059 to 0.178, p < 0.001). Overall, the findings underscore the dual role of SCPs as both facilitators of engagement and sources of psychological strain, emphasizing the necessity of sustainable digital marketing strategies that prioritize user well-being. These insights offer valuable implications for academic researchers and industry practitioners, suggesting that integrating SDT and IOT can advance our understanding of the multifaceted relationships among FoMO, platform usage, and psychological health in the digital era.
Keywords: Social networking (online); Psychology; Anxiety disorders; Addiction; Real-time systems; Fatigue; Electronic commerce; Depression; Web sites; Peer-to-peer computing; Fear of missing out (FoMO); informational incentives; nomophobia; problematic social media use; psychological anxiety; self-determination theory; social commerce; FACEBOOK USE; MEDIA ENGAGEMENT; YOUNG-ADULTS; FIT INDEXES; FEAR; ONLINE; SELF; ADOLESCENTS; ANXIETY; Computer Science; Engineering; Telecommunications